Monitoring Urban Growth: The Case of Burayu Town, Oromia Regional State of Ethiopia - Abebe, Birhanu Girma; Gemeda, Bedane Shata; Amare, Agemasie Gebeyehu (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2024)
Due to the presence of a low level of urbanization in developing countries, the horizontal expansion of cities/towns is obvious and results in a rapid rate of urbanization. To monitor the horizontal expansion/growth of the Burayu town from 1986 to 2020 and forecasting by 2030, a time series and high-resolution aerial and satellite images were used. Besides, GIS tools and techniques were applied to organize and analyze the data. Results indicate that the town of Burayu horizontally expanded by 6,331 Ha from year 1986 to 2020; and will expand doubly by 2030.To monitor the growth/ expansion of towns and cities of the urban extent, the town administration and decision-makers should promote; the compact city and mixed-use principles, as well as the regional planning approaches.